ANALISIS PROSES REKRUTMEN CALON KARYAWAN DENGAN MENGGUNAKAN METODE DISC PERSONALITY TEST PADA PT. GRHA HUMANINDO MANAJEMEN PROYEK GAPURA ANGKASA BANDARA INTERNASIONAL SULTAN MAHMUD BADARUDDIN II PALEMBANG - Hendra Musa (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
This research to analyze the recruitment system for prospective employees in accordance with the standards and criteria for employees at PT Grha Humanindo Manajemen. The system used in the recruitment of prospective employees at PT. Grha Humanindo Management is the DISC Personality Test method. This research is descriptive qualitative in order to describe how the process of implementing employee recruitment in accordance with the standards and criteria for employees desired by PT Grha Humanindo Manajemen using the DISC Personality Test method. The results showed the DISC Personality Test method has been running in accordance with the standards set by the company by prioritizing the attitude value in order to achieve employees who have service standards. The results also show this method cannot provide a description of a person's skills and level of knowledge. Considering that this company is engaged in the service sector, the deficiencies in the DISC method are not a priority. DISC Personality Test method can prevent parties who intend to intervene in the recruitment process, including committing bribes or collusion, corruption and nepotism.